INFLASI DALAM PRESPEKTIF ISLAM (ANALISIS TERHADAP PEMIKIRAN AL-MAQRIZI) - Awaluddin Awaluddin (Institut Agama Islam Negeri Batusangkar, 2017)
Inflation is one of the macroeconomic symptoms associated with the decline in exchange rates (money) on goods and services market. One of the leaders of Islamic economics who specializes in his discussion of macroeconomics is al-Maqrizi. The solution offered by al-Maqrizi related to the problems that occurred in Egypt is to use the natural monetary system, the dinar and dirham become the base currency, while the fulus is published in a limited and only to buy trivial goods. Al-Maqrizi set the relative price for dinar, dirham and fulus. The relative price of dinar and dirham is 1:24, while the relative price between dirham and fulus is 1: 140. In addition to providing solutions to address the above three issues, al-Maqrizi also proposed solutions in a social perspective. This gives the conclusion that the impact of the economic crisis depends on the nature of income and wealth of each group. If the income is fixed or inflated but lower than the rate of inflation, then the condition is severe. Conversely, if their income rises higher than the rate of inflation, then their material welfare increases. Likewise with wealth in the form of money, they suffered losses because their purchasing power continued to decrease and they also had to increase the cost to meet the demands of the ever-increasing need.